Peroxisome proliferator-activated receptors in metabolic and renal health: a comprehensive review - Vahora, Nazmi; Yathindra, Meenakshi Reddy; James, Deepa Maria; Sharma, Rahul; Panvalkar, Ajit Sneha Shrikant; Shyam, Gayathri; N. L., Swathi (International Journal of Research in Medical Sciences, 2025)
Peroxisome Proliferator-Activated Receptors (PPARs), including α, β/δ and γ isoforms, play crucial roles in regulating metabolic and renal health. This study explores their involvement in lipid metabolism, inflammation, chronic kidney disease (CKD) and diabetic nephropathy, emphasizing the therapeutic potential of both synthetic and natural PPAR agonists. A comprehensive literature review was conducted using PubMed, Scopus and Google Scholar, with search terms such as "Peroxisome Proliferator-Activated Receptors," "PPAR agonists," "lipid metabolism," "chronic kidney disease," and "diabetic nephropathy." Boolean operators and MeSH terms were applied and studies from 2000 to 2024 were included. Eligibility criteria focused on experimental, clinical and review articles detailing PPAR mechanisms, physiological roles and therapeutic applications. Findings indicate that PPARs are critical in lipid and glucose metabolism, oxidative stress reduction and fibrosis mitigation. Synthetic ligands such as thiazolidinediones and fibrates demonstrate therapeutic efficacy in CKD and metabolic syndrome, though challenges such as side effects and variability persist. While PPAR-targeted treatments offer promise in metabolic and renal disorders, their clinical application requires further refinement through selective modulators, combination therapies and biomarker-guided strategies.